Copper Modulates the Catalytic Activity of Protein Kinase CK2 - Chojnowski, John E.; Li, Rongrong; Tsang, Tiffany; Alfaran, Fatimah H.; Dick, Alexej; Cocklin, Simon; Brady, Donita C.; Strochlic, Todd I. (Frontiers in Molecular Biosciences, 2022)
Casein kinase 2 (CK2) is an evolutionarily conserved serine/threonine kinase implicated in a wide range of cellular functions and known to be dysregulated in various diseases such as cancer. Compared to most other kinases, CK2 exhibits several unusual properties, including dual co-substrate specificity and a high degree of promiscuity with hundreds of substrates described to date. Most paradoxical, however, is its apparent constitutive activity: no definitive mode of catalytic regulation has thus far been identified. Here we demonstrate that copper enhances the enzymatic activity of CK2 both in vitro and in vivo. We show that copper binds directly to CK2, and we identify specific residues in the catalytic subunit of the enzyme that are critical for copper-binding. We further demonstrate that increased levels of intracellular copper result in enhanced CK2 kinase activity, while decreased copper import results in reduced CK2 activity. Taken together, these findings establish CK2 as a copper-regulated kinase and indicate that copper is a key modulator of CK2-dependent signaling pathways.